ChemInform Abstract: Enantioselective Friedel—Crafts Alkylation of Indoles with (E)‐1‐Aryl‐4‐benzyloxybut‐2‐en‐1‐ones Catalyzed by an (R)‐3, 3′‐Br2BINOLate—Hafnium(IV) Complex. Issue 35 (8th August 2013) - Blay, Gonzalo; Fernandez, Isabel; Munoz, M. Carmen; Pedro, Jose R.; Vila, Carlos
Abstract This method uses N‐unprotected indoles.